Engaging patients and informal caregivers to improve safety and facilitate person- and family-centered care during transitions from hospital to home – a qualitative descriptive study - Backman, Chantal (Patient Prefer Adherence, 2019)
Purpose: The purpose was to describe patients and informal caregivers’ perspectives on how to improve and monitor care during transitions from hospital to home as part of a larger research study to prioritize the components that most influence the development of successful care transition interventions. Methods: We conducted a qualitative descriptive study between July and August 2016, during which time semi-structured telephone interviews (n=8) were completed with patients and informal caregivers across select Canadian provinces. Interviews were audio-recorded, transcribed and thematically analyzed. Results: Main themes included: the need for effective communication between providers and patients and informal caregivers; the need for improving key aspects of the discharge process; and increasing patients and informal caregivers involvement in care practices. Participants also provided suggestions on how to best monitor care transitions. Conclusion: This study highlighted the following strategies with patients and informal caregivers: focus on effective communication regarding important information; provide appropriate resources; and increase involvement. Future research is needed to incorporate the input from patients and informal caregivers into the design and implementation of care transition interventions.